A Analisis Kinerja Keuangan Bank BTPN Syariah Periode 2019-2021 - Ghina Azizah, Jihan; Umiyati; Obrian, Dea Diva; Zahiranita, Delia Putri (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
This research analyzes the financial performance of Bank BTPN Syariah during the 2019-2023 period using the RGEC, Altman Z-Score and DEA methods. The results show that Bank BTPN Syariah has a capital adequacy level (CAR) that is consistently above regulatory standards, reflecting strong stability. An average technical efficiency level of 81% indicates good resource management, although there are variations in efficiency across years. Z-Score analysis shows an improving trend of stability in 2023, but still requires further strengthening. Bankruptcy predictions using the Altman Z-Score placed banks in the